Latissimus Dorsi Transposition in Supraspinatus Tendon Retraction (Patte III) and Thomazeau Grade 3 Fatty Degeneration (Clinical Case) - N. S. Ponomarenko; V. V. Monastyrev; I. A. Kuklin (Acta Biomedica Scientifica, 2019)
Introduction. The proportion of injuries of the rotational cuff is from 65 to 84 % of all injuries of the shoulder joint. This pathology is more often registered in people over 60 years old. It is far from always that during initial visits, patients are given the correct diagnosis. Most patients are treated conservatively with short-term improvement or without dynamics. The main diagnostic method is an MRI of the shoulder joint, where we can see soft tissue structures. The proportion of massive rupture of the tendons of the supraspinatus muscle is 10-40 % of all ruptures of the rotator cuff.The more time passes from the moment of injury to surgical treatment, the more pronounced are the retraction and degenerative changes in tendons. A special category is occupied by patients with chronic rupture of the tendon of the supraspinatus muscle with a retraction of more than 5 cm (Patte grade III) and Thomazeau grade 3 fatty degeneration.In this category of patients, it is not possible to re-insert the tendons of the rotational cuff of the shoulder.Objective: to evaluate the clinical effectiveness of surgical treatment of a patient with retinal tendon retraction (Patte grade III) and Thomazeau grade 3 fatty degeneration.Materials and methods. The clinical case is presented: a man with a chronic total rupture of the tendon of the supraspinatus, infraspinatus muscle (Patte grade III) and Thomazeau grade 3 fatty degeneration. Secondary upper subluxation of the head of the humerus is revealed. The patient underwent surgical treatment: transposition of the latissimus dorsi muscle on the large tubercle of the humerus.Results. Six months after the operation, the patient restored the function of the upper limb, pain was stopped. Conclusion. Given the functional result, transposition of the latissimus dorsi tendon can be considered the technique of choice for inoperable tendon rupture of the supraspinatus muscle.